Preventing extremism through education: exploring impacts and implications of counter-radicalisation efforts - Sjøen, Martin M. (Journal of beliefs and values, 2019)
The counter-radicalisation efforts that have swept through much of the world seem to have placed schools and universities at the forefront of global counterterrorism. In this article, we review research to explore the impacts and implications of preventing radicalisation and violent extremism through education. We synthesised themes from the literature in relation to intervention models that differentiate between primary, secondary and tertiary prevention levels, in order to embrace the heterogeneity and complexity of radicalisation issues. Research is at an early stage in trying to make sense of the 'causes and cures' of radicalisation in the context of young people and education; yet our review suggests that educators should approach prevention through humanistic, relational and inclusive pedagogics. However, counter-radicalisation efforts tend to result in the use of 'harder' prevention strategies, which can have quite negative impacts on education. Although scholarly output is growing, effectiveness evidence on these issues remains weak. More consideration should be given to study how the counter-radicalisation discourse is merged with education, and with what consequences.